Hacking : computer hacking beginners guide how to hack wireless network, basic security and penetration testing, kali linux, your first hack - Norman, Alan T. ([United States] : [publisher not identified], 2017)
This book covers the basics of everything you need to know about hacking.
What is hacking? -- Vulnerabilities and exploits -- Getting started -- The hacker's toolkit -- Gaining access -- Malicious activity and code -- Wireless hacking -- Your first hack -- Defensive security & hacker ethics -- Make your own keylogger in C++ -- Setting up the environment -- Setting the eclipse environment: -- Programming basics (Crash course on C++) -- Typical program -- Pointers and files -- Basic keylogger -- Upper and lower case letters -- Encompassing other characters -- Hide keylogger console window.
CSE
Karim International
Keywords: Computer security; Hacking; Computer programming; Computer science